LOS PROGRAMAS INFORMÁTICOS DE SUBTITULACIÓN EN LA ENSEÑANZA/APRENDIZAJE DE LA TAV DENTRO DEL ÁMBITO UNIVERSITARIO (2): ANÁLISIS DEL SOFTWARE PROFESIONAL - Roales Ruiz, Antonio (Entreculturas. Revista de traducción y comunicación intercultural, 2016)
The aim of this paper is to show the analysis accomplished on seven subtitling programs. All of them are professional software. We have been investigating whether these programs are suitable for teaching and learning how to create subtitles.